2022
DOI: 10.1172/jci.insight.159254
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma chemoprevention by targeting the angiotensin-converting enzyme and EGFR transactivation

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of death among cirrhotic patients, for which chemopreventive strategies are lacking. Recently, we developed a simple human cell-based system modeling a clinical prognostic liver signature (PLS) predicting liver disease progression and HCC risk. In a previous study, we applied our cell-based system for drug discovery and identified captopril, an approved angiotensin converting enzyme (ACE) inhibitor, as a candidate compound for HCC chemoprevention. Here, we expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…The HBx promotes cell proliferation by disturbing the cross-talk between PTEN and miR-181a in HBV-related hepato-carcinogenesis ( Tian et al, 2017 ). EGFR ( Crouchet et al, 2022 ) and HDAC1 ( Rivas et al, 2021 ) have a role in promoting hepatocarcinogenesis. The upregulation of EGFR promotes the progression of HCC and leads to sorafenib resistance ( Pang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HBx promotes cell proliferation by disturbing the cross-talk between PTEN and miR-181a in HBV-related hepato-carcinogenesis ( Tian et al, 2017 ). EGFR ( Crouchet et al, 2022 ) and HDAC1 ( Rivas et al, 2021 ) have a role in promoting hepatocarcinogenesis. The upregulation of EGFR promotes the progression of HCC and leads to sorafenib resistance ( Pang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of antihypertensive drugs, which include angiotensin-converting enzyme inhibitors (ACEi), calcium channel blockers (CCBs), beta-adrenoceptor blockers (BBs), angiotensin receptor blockers (ARBs) and thiazide diuretics, is a critical component in MASLD management, since hypertension showed an independent association with HCC risk and poor prognosis ( 117 ). Nonetheless, it is still unclear whether and how antihypertensive drugs may modify the risk of HCC or may limit the efficacy of anti-cancer therapies ( 118 , 119 ). For instance, captopril, an ACEi, reduced hepatic fibrosis and prevented progression towards HCC development in murine models of liver cancer ( 119 ).…”
Section: Cardiovascular Risk In Patients Affected By Masld-hccmentioning
confidence: 99%
“…8 An ACEI, captopril, suppresses fibrogenic and inflammatory pathways such as EGFR signaling, reverses high-risk PLS, and reduces HCC nodules in chemical- and diet-induced rat models of NAFLD-driven HCC. 109 A small meta-analysis of cohort studies showed that use of ACEIs/ARBs was associated with lower HCC risk (RR, 0.51; 95% CI, 0.44–0.60). 110 In a subsequent nested case–control study from Korea, use of ARBs at 30 cDDD or higher showed inverse association with presence of HCC (aOR, 0.65; 95% CI, 0.43–0.97).…”
Section: Potential Hcc Chemoprevention Therapies With Generic Agentsmentioning
confidence: 99%